2016
DOI: 10.1089/scd.2016.0048
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the Differences of Secretome of Human Bone Marrow Mesenchymal Stem Cells, Adipose Tissue-Derived Stem Cells, and Human Umbilical Cord Perivascular Cells: A Proteomic Analysis

Abstract: The use of human mesenchymal stem cells (hMSCs) has emerged as a possible therapeutic strategy for CNS-related conditions. Research in the last decade strongly suggests that MSC-mediated benefits are closely related with their secretome. Studies published in recent years have shown that the secretome of hMSCs isolated from different tissue sources may present significant variation. With this in mind, the present work performed a comparative proteomic-based analysis through mass spectrometry on the secretome of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
144
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 188 publications
(152 citation statements)
references
References 73 publications
(90 reference statements)
8
144
0
Order By: Relevance
“…MSCs secretomes present a high range of molecules, such as cytokines and growth factors 11, 3032 . BDNF is a neurotrophin that, together with TrkB, its cognate receptor, is present throughout CNS 33 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MSCs secretomes present a high range of molecules, such as cytokines and growth factors 11, 3032 . BDNF is a neurotrophin that, together with TrkB, its cognate receptor, is present throughout CNS 33 .…”
Section: Discussionmentioning
confidence: 99%
“…HUCPVC secretome present on its composition a wide range of molecules with different properties 31, 32 . Although our data shows a complete reversion of CM-induced axonal outgrowth when BDNF is depleted from the media, we cannot exclude the possibility that other factors present in HUCPVC secretome might also induce axonal outgrowth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was showed that stem cells derived from bone marrow, adipose tissue, and umbilical cord secrete 134 neuro‐regulatory molecules common to all three population. Still, 140 proteins were specific for stem cells isolated from fetal sources [Pires et al, ]. Pattern of protein expression was also modulated when culture conditions were changed from static to dynamic [Teixeira et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…By profiling MSCs secretome characterization, it was found the presence of many cytokines, chemokines, Trubiani et al (2016) and growth factors through which MSCs promote neuronal survival increases process of neurogenesis and angiogenesis, modulate immune response, and inhibit neuronal cell death/apoptosis (Pires et al 2016). In addition to soluble factors, extracellular vesicles were found to be a key factors in cell-cell communication (Mittelbrunn and SanchezMadrid 2012).…”
Section: Bone Marrow-derived Mscsmentioning
confidence: 99%